Auditor‐provided nonaudit services: Post‐EU‐regulation evidence from Denmark. Issue 1 (9th August 2018) - van Liempd, Dennis; Quick, Reiner; Warming‐Rasmussen, Bent
Abstract : This survey study focuses on the relationship between the simultaneous provision of audit and nonaudit services and auditor independence‐in‐appearance as perceived by Danish stakeholders. Thereby, the perceived usefulness of the new EU public‐interest entity regulation and audit directive is evaluated. Our findings indicate that the joint provision of nonaudit and audit services is negatively associated with perceived auditor independence. However, this differs according to the type of stakeholder group. Many individual services, even those not on the EU blacklist, are regarded as problematic. Nevertheless, the relation to independence‐in‐appearance differs by type of service. The EU cap on nonaudit services fees seems to be too high. The separation between audit firms' staff that provides auditing services and staff that provides nonaudit services, and an approval of nonaudit services by the audit committee, are not regarded as helpful in enhancing auditor independence. Finally, respondents see a need to expand the strict EU regulations for audits of public‐interest entities to audits of large non‐public‐interest entities.